Entwicklung der Erdölindustrie in Nigeria - unter besonderer Berücksichtigung der Auswirkungen des Bürgerkrieges - Schätzl, Ludwig (ERDKUNDE, 1970)
The development of the oil industry in Nigeria, with special reference to the effects of the civil war. Extensive deposits of crude oil occur in the south Nigerian sedimentary depression, in the area of the Niger delta and on the continental shelf off the coast. Commercial oil production began in December 1957. Up to the middle of 1967 production had risen to almost 2,4 million tons per month (about 600,000 bbl/ day) and Nigeria ranked 11th in the list of world oil-producing states. The oil industry developed into one of the country's most important exporters. In 1966, one-third of Nigeria's total exports were accounted for by crude oil and one-ninth of Federal revenue came from oil exploration and production companies. In addition, the oil industry stimulated the economic growth process, particularly in the Port Harcourt area before the war. The national refinery constructed in 1965 largely satisfied the domestic demand for mineral oil end-products and the oil-fields gas produced as the joint product of oil extraction provides a cost-advantageous energy source for electricity generation and for energy intensive industrial plants. The vigorous development of the Nigerian oil industry was interrupted in mid-1967 by the outbreak of the civil war. Production was reduced to one-twelfth of the pre-war level. The military successes of the Federal Government enabled it to win back control over the oilfields. Since the end of 1968, crude oil production has climbed again and the pre-war peak was reached again as early as March 1969. The loss in production foregone by the Nigerian oil industry in this time is calculated at about 45 million tons, corresponding to an expert loss of about N 220 million. Despite acts of sabotage and air attacks by secessionist 'Biafra', the investment level of the oil companies reached a peak in 1969. The main focus of new development has shifted from the east to the middle west and to offshore concession areas. Assuming that the oil industry can continue without disruptive interruptions from the war, the oil companies reckon to raise production by 1973 to 2 million bbl/day (100 million tons per annum). The oil industry will contribute decisively to the repair of war damage and, in the long term, to the economic recovery of Nigeria.